Dynamic roles of tumor-infiltrating B lymphocytes in cancer immunotherapy - Shishengnan Song; Chong Wang; Yangchao Chen; Xiaorong Zhou; Yi Han; Haijian Zhang (Cancer Immunology, Immunotherapy)
Abstract The amazing diversity of B cells within the tumor microenvironment is the basis for the diverse development of B cell-based immunotherapies. Here, we focus on elucidating the mechanisms of tumor intervention mediated by four tumor-infiltrating B lymphocytes. Naive B cells present the initial antigen, germinal center B cell subsets enhance antibody affinity, and immunoglobulin subtypes exert multiple immune effects, while regulatory B cells establish immune tolerance. Together they reflect the complexity of the changing dynamics of cancer immunity. Additionally, we have investigated the dynamic effects of tumor-infiltrating B lymphocytes in immunotherapy and their relationship to prognosis, providing new insights into potential treatment strategies for patients.